VAKSIN (Animated Video for Online Learning System): Support for Independent Asynchronous Learning in Introductory Geometry Courses through SIPEJAR - Utami, Anita Dewi; Suwarman, Ramdhan Fazrianto; Darmawan, Puguh; Listiawan, Tomi; Rofiki, Imam (Jurnal Pendidikan Edutama, 2024)
This research study is focused on developing the VAKSIN (Animated Video for Online Learning System) design, which aims to facilitate independent asynchronous learning in the introductory geometry course. The research methodology employed is based on Plomp's general educational problem-solving model, involving three out of five phases: initial investigation, design, and realization phases. Subsequent studies are planned to include testing, evaluation, revision, and implementation phases. The findings of the research indicate the feasibility of using VAKSIN in the Introductory Geometry course.